Bentuk Kandoushi (Kata Seru) yang Menyatakan Outou (Jawaban) - Ilvan Roza (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2008)
People use many kinds of utterances in their daily activities that involve speakin. One of the utterances is interjection. This particular utterance is used to express the emotional feeling to the listener. Generally, interjections are used in spoken language except the using the novel or comics. One of the expressions of interjection is “outou” (answer). This is an expression to see the respond or answer from the listener. The expression can be a comment or reaction towards the listener’s opinion and demand. Keywords: “kandoushi” (interjection words), “outou” (jawaban).